A molecular phylogenetic framework for the subfamily Ocenebrinae (Gastropoda, Muricidae). (27th September 2016) - Barco, Andrea; Herbert, Gregory; Houart, Roland; Fassio, Giulia; Oliverio, Marco
Abstract : The Ocenebrinae is a subfamily of marine predatory gastropods known as oyster and mussel drills. Their current phylogenetic framework is traditionally based on shell and radular characters, but a consensus on relationships among genera is still lacking. We investigated the molecular phylogeny of Ocenebrinae using 50 species and DNA data from one nuclear (28S) and two mitochondrial (COI and 16S) genes, the largest data set so far assembled for this subfamily. We found support for the monophyly of the Ocenebrinae, and species were divided into four major lineages. Within groups, genera had similar geographic distributions, suggesting that except in a few cases, species diversification within clades occurred without range expansions. We discuss the phylogenetic distribution of a labral tooth and a sealed siphonal canal, two characteristic ocenebrine features. We also show that Ocinebrina species in the north‐eastern Pacific are not monophyletic with north‐eastern Atlantic and Mediterranean species, and that the Ocinebrina edwardsii species complex belongs to Ocenebra .